L’empire des institutions(et leurs crises) - Frédéric Lordon (Revue de la Régulation)
Social sciences have long addressed the issue of the effects of institutions, less the issue of how these effects are produced. How do institutions concretely normalize agents? A spinozist view in social sciences is especially well geared to answer that kind of question insofar as it offers concepts to think efficacy – understood as the production of effects. These concepts are power (conatus) and affects. Making something to individuals and making them do something is pertaining to power as an ability to affect. Indeed institutions make something to individuals – they affect them. Being social realities, a spinozist theory of institutions has to consider these concepts at a collective level. They then take the form of the “power of the multitude” which appears to be the fundamental principle of any institution norm or authority.